Gender Representation in the EASL Liver Cancer Summit 2023: Assessing Progress and Challenges - da Silva Vieira, Laynara Vitoria; De Araújo França, Bárbara Nissara (Jornal de Ciências da Saúde do Hospital Universitário da Universidade Federal do Piauí, 2023)
Background: Women are numerically underrepresented in the field of gastroenterology and hepatology. This study aims to characterize gender representation during the EASL Liver Cancer Summit 2023. Methods: Using data available on the LCS2023 online platform, we compared the distribution of moderators, speakers, and debaters in the Plenary and Industry Sessions. Descriptive statistical analysis was conducted using R Software 4.3.0. Results: In 75% (n=18) of the sessions, women were underrepresented, comprising less than 50% of the total speakers, debaters, or moderators. Conclusion: There is a gender disparity in the oral sessions, predominantly composed and mediated by men. Additionally, the study highlighted the need to broaden the discussion and identify mechanisms for greater inclusion and retention of women in hepatology careers.